VD_FINDINFO HC / 2017 / 464 vom 12. Mai 2017 - VD Tribunal cantonal (2017)
OBLIGATION D'ENTRETIEN, MINIMUM VITAL, TRAIN DE VIE, ENFANT, MAJORITÉ{ÂGE}, REVENU HYPOTHÉTIQUE, ÉPARGNE, FORTUNE | 163 al. 1 CC, 176 al. 1 CC, 106 al. 1 CPC (CH)